Impara online a risolvere i problemi di passo dopo passo. Solve the quadratic equation n^2+12n=-20. Applicare la formula: x^2+bx=x^2+bx+\left(\frac{b}{2}\right)^2-\left(\frac{b}{2}\right)^2, dove b=12, bx=12n, x=n, x^2+bx=n^2+12n e x^2=n^2. Applicare la formula: x^2+bx+f+g=\left(x+\sqrt{f}sign\left(b\right)\right)^2+g, dove b=12, bx=12n, f=36, g=-36, x=n, x^2+bx=n^2+12n+36-36 e x^2=n^2. Applicare la formula: x+a=b\to x+a-a=b-a, dove a=-36, b=-20, x+a=b=\left(n+6\right)^2-36=-20, x=\left(n+6\right)^2 e x+a=\left(n+6\right)^2-36. Applicare la formula: x+a+c=b+f\to x=b-a, dove a=-36, b=-20, c=36, f=36 e x=\left(n+6\right)^2.